Faktor-Faktor yang Mempengaruhi Impor Indonesia, 2000.I-2008.I - Nunik Rifa'atul Mahmudah; Dijan Rahajuni (EKO-REGIONAL, 2011)
The aim of this research are to enquiry the influence of exchange rate rupiah to USD, Gross Domestic Product (GDP), and world oil price toward import of Indonesia during 2000.I-2008.I. The research methods are descriptive and quantitative analyses using secondary data. The analysis tool is path analysis to show direct and indirect influences of Indonesia’s import. This research also uses t-test to show partial influence and F-test to know together influence. Between those three variables, world oil price is the most influence variable of Indonesia's import.                           Keywords: exchange rate, import, gross domestic product, world oil price